PENGEMBANGAN MATERI AJAR TEKS DESKRIPSI BERBANTUAN CAPCUT DI KELAS VII SMP MUHAMMADIYAH 1 MEDAN - Geprita Gulo; Atika Wasilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the limited use of digital media and low motivation of students in learning to write descriptive texts at the junior high school level. This study aims to develop and test the feasibility of descriptive text teaching materials assisted by the CapCut application for grade VII students of SMP Muhammadiyah 1 Medan. The method used is research and development (R&D) with a 4D model that includes the stages of definition, design, development, and dissemination. Data collection techniques were carried out through observation, interviews, and questionnaires involving 27 students and validation by material experts, media experts, and subject teachers. The results of the needs analysis showed that 100% of students were interested in video-based learning, 96.2% stated that teachers had not used video media, and 88.8% stated that they needed video-based teaching materials. The resulting product is a video teaching material that combines text, audio, images, and animation using the CapCut application. Validation results showed that the feasibility percentage was 84.7% among material experts, 84% among media experts, and 97.5% among subject teachers. With an average rating of 88.7%, it can be concluded that the product in this study is very good/very suitable for use by teachers and students in learning. The results of this study indicate that the use of video-based media assisted by CapCut can increase student motivation and understanding in writing descriptive texts and is an effective alternative teaching material.